2020
DOI: 10.1111/raq.12513
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome diversity and dysbiosis in aquaculture

Abstract: With the continuous growth of the human population and associated need for high‐quality protein, the aquaculture sector will be required to increase significantly in productivity. This growth in productivity will be achieved through more efficient use of resources like feeds, genetic improvement and limiting the impacts of disease. One of the key links between animal productivity and disease is that of microbial diversity, with high‐throughput sequencing technologies increasing our understanding of the role mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 156 publications
2
68
0
Order By: Relevance
“…Lastly, although it is not the major aim of the present study, understanding the underlying mechanisms responsible for the divergence of gut microbiome between the wild and farmed fishes can also provide key information on improving production of aquaculture [21]. Dysbiosis has been widely reported in the aquaculture fishes fed with formulated feed [79]. Our study revealed possible dysbiosis in farmed croaker since potential pathogenic bacterial taxa, such as Vibrio spp., Photobacterium spp.…”
Section: Discussionmentioning
confidence: 71%
“…Lastly, although it is not the major aim of the present study, understanding the underlying mechanisms responsible for the divergence of gut microbiome between the wild and farmed fishes can also provide key information on improving production of aquaculture [21]. Dysbiosis has been widely reported in the aquaculture fishes fed with formulated feed [79]. Our study revealed possible dysbiosis in farmed croaker since potential pathogenic bacterial taxa, such as Vibrio spp., Photobacterium spp.…”
Section: Discussionmentioning
confidence: 71%
“…The study of the gut microbiota has received great attention in the aquaculture sector as an indicator of productivity and fish health, and it is likely that its manipulation will be achieved in the near future in several fish species of commercial interest. Several studies have recently addressed the effect of diet (Huyben et al, 2020;Rimoldi et al, 2020), rearing density (Parma et al, 2020), age, sex (Piazzon et al, 2019), and genetic background (Piazzon et al, 2020) on the gut microbiota of gilthead sea bream; however more studies to detect dynamical changes of microbial composition during the farming cycle are necessary (Infante-Villamil et al, 2020). In the present study, at high phylogenetic levels, the overall gut microbiome structure was similar among groups, and the main represented taxa at phylum (Firmicutes, Proteobacteria, and Actinobacteria) and family (Lactobacillaceae) levels are consistent with previous trials on this species reared on similar aquafeed formulation and feeding protocols (Parma et al, 2016(Parma et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The GIT microbiome composition shapes host physiology and growth, but these functions in aquatic animal hosts have not yet been fully investigated. Only a limited number of studies have evaluated the association between the fish microbiota and production outcomes in aquaculture settings [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%